La música ecuatoriana como contenido en la enseñanza de la flauta traversa y su incidencia en la receptividad de los estudiantes del nivel inicial del conservatorio de música “Salvador Bustamante Celi” de la ciudad de Loja. Propuesta alternativa - Morocho Plascencia, Betty Janina (2015)
This research work entitled "The Ecuadorian music and content in teaching the flute and its impact on the receptivity of the students of the initial level of Conservatory" Salvador Bustamante Celi "city of Loja." Proposed alternative. He had has objective is to develop a text introduction to the flute, based on Ecuadorian music; aimed at students of the Initial Level of Music "Salvador Bustamante Celi". The technical elements of the survey of 16 students flute and interview, conducted at 2 teachers flute and 2 authorities, rector and vice-rector of the Conservatory of Music "Salvador Bustamante Celi" was used in order to obtain data city. The results obtained were socialized in the Conservatory of Music "Salvador Bustamante Celi" in the theater of the institution, through a forum between students, teachers and officials from the National University of Loja and the Conservatory. A study method was presented, the same as students flute Initial level of Music "Salvador Bustamante Celi" was applied, yielding positive effects on the development of technical and instrumental performance